Pemanfaatan Limbah Fine Polymer PT Polytama Propindo Menjadi Paving Block Menggunakan Pendekatan DPSIR - Afnaldi Afnaldi; Muchamad Agung Wicaksono; Findri Puspita Sari; Bernard Hasibuan (Journal of Innovative and Creativity (Joecy), 2026)
The polypropylene production process generates a by-product in the form of fine polymer, which represents the second-largest source of non-hazardous and non-toxic solid waste generated by the company. This study aims to analyze the success of the Batik Javing (Plastic Material into Paving) Program innovation using the DPSIR (Drivers, Pressures, States, Impacts, Responses) framework. This research employs a qualitative-quantitative descriptive approach through the DPSIR environmental evaluation framework and the application of Design Thinking principles within a circular economy model. The program implementation successfully reduced fine polymer waste generation significantly, from 25.66 tons in 2020 to only 3.04 tons in 2023. Furthermore, the program established a circular economy model that reduced production costs for paving block artisans in the Ring 1 area through the substitution of sand materials. The Batik Javing innovation has proven effective in reducing industrial waste while simultaneously strengthening the socio-economic empowerment of local communities in a sustainable manner.